MXene (Ti3C2) Vacancy-Confined Single-Atom Catalyst for Efficient Functionalization of CO2 - Zhao, Di; Chen, Zheng; Yang, Wenjuan; Liu, Shoujie; Zhang, Xun; Yu, Yi; Cheong, Weng-Chon; Zheng, Lirong; Ren, Fuqiang; Ying, Guobing; Cao, Xing; Wang, Dingsheng; et al. (Journal of the American Chemical Society, 2019)
A central topic in single-atom catalysis is building strong interactions between single atoms and the support for stabilization. Herein we report the preparation of stabilized single-atom catalysts via a simultaneous self-reduction stabilization process at room temperature using ultrathin two-dimensional Ti3–x C2T y MXene nanosheets characterized by abundant Ti-deficit vacancy defects and a high reducing capability. The single atoms therein form strong metal–carbon bonds with the Ti3–x C2T y support and are therefore stabilized onto the sites previously occupied by Ti. Pt-based single-atom catalyst (SAC) Pt1/Ti3–x C2T y offers a green route to utilizing greenhouse gas CO2, via the formylation of amines, as a C1 source in organic synthesis. DFT calculations reveal that, compared to Pt nanoparticles, the single Pt atoms on Ti3–x C2T y support feature partial positive charges and atomic dispersion, which helps to significantly decrease the adsorption energy and activation energy of silane, CO2, and aniline, thereby boosting catalytic performance. We believe that these results would open up new opportunities for the fabrication of SACs and the applications of MXenes in organic synthesis.